Formation of the bilingual personality of a child in the family: philosophical reflection - EFLOVA, M.; MAXIMOVA, O. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The present paper discusses the formation of a bilingual environment that builds the child’s personality in the family space. The authors substantiate the thesis that, in modern conditions of linguistic diversity and intensive mutual influence of various languages, the command of several languages is an essential condition for the development of thought and a guarantee for dialogue in the space of different ethnic groups. The criteria for conceiving a thought in a language is the ability to formulate sentences or texts directly in a given language, as opposed to a translation of a statement, previously constructed in another language. RESUMEN El presente documento discute la formación de un entorno bilingüe que construye la personalidad del niño en el espacio familiar. Los autores corroboran la tesis de que, en condiciones modernas de diversidad lingüística e influencia mutua intensiva de varios idiomas, el dominio de varios idiomas es una condición esencial para el desarrollo del pensamiento y una garantía para el diálogo en el espacio de diferentes grupos étnicos. Concebir un pensamiento en un idioma es la capacidad de formular oraciones o textos directamente en un idioma dado, en lugar de una traducción de un enunciado, previamente construido en otro idioma.